The sensitivity, specificity, predictive values, and likelihood ratios of fecal occult blood test for the detection of colorectal cancer in hospital settings - Elsafi, Salah H (Clin Exp Gastroenterol, 2015)
OBJECTIVES: To study the performance of a single test using two fecal occult blood tests with colonoscopy for the detection of colorectal cancer (CRC) for the first time in Saudi Arabia to determine possible implications for the anticipated colorectal screening program. MATERIALS AND METHODS: We compared the performance of guaiac and immunochemical fecal occult blood tests for the detection of CRC among patients of 50–74 years old attending two hospitals in the Eastern Region of Saudi Arabia. Samples of feces were collected from 257 asymptomatic patients and 20 cases of confirmed CRC, and they were tested simultaneously by the guaiac-based occult blood test and monoclonal antibody-based immunoassay kit. Colonoscopy was performed on all participants and the results were statistically analyzed with both positive and negative occult blood tests of both methods. RESULTS: Of the 277 subjects, 79 tested positive for occult blood with at least one method. Overall, the number of those with an occult blood-positive result by both tests was 39 (14.1%), while for 198 (71.5%), both tests were negative (P<0.0001); 40 (14.4%) samples showed a discrepant result. Colonoscopy data were obtained for all 277 patients. A total of three invasive cancers were detected among the screening group. Of the three, the guaiac test detected two cases, while the immunochemical test detected three of them. Of the 20 control cases, the guaiac test detected 13 CRC cases (P=0.03), while the immunochemical test detected 16 of them (P<0.0001). The sensitivity of guaiac and immunochemical tests for the detection of CRC in the screening group was 50.00% (95% confidence interval [CI] =6.76–93.24) and 75.00% (95% CI =19.41–99.37), respectively. For comparison, the sensitivity of the guaiac fecal occult blood test for detecting CRC among the control group was 65.00% (95% CI =40.78–84.61) while that of FIT was 80.00% (95% CI =56.34–94.27). The specificity of the guaiac and immunoassay tests was 77.87% (95% CI =72.24–82.83) and 90.12% (95% CI =85.76–93.50), respectively. The positive likelihood ratio of guaiac and immunochemical tests for the detection of CRC was 2.26 (95% CI =0.83–6.18) and 7.59 (95% CI =3.86–14.94), whereas the negative likelihood ratio was 0.64 (95% CI =0.24–1.71) and 0.28 (95% CI =0.05–1.52), respectively. The positive predictive values of guaiac and immunochemical tests were 3.45% (95% CI =0.426–11.91) and 10.71% (95% CI =2.27–28.23), respectively. There was no marked difference in the negative predictive values for both methods. The sensitivity of the fecal occult blood test by FIT was significantly higher for stages III and IV colorectal cancer than for stages I and II (P=0.01) and it was insignificant for the guaiac fecal occult blood test (P=0.07). CONCLUSION: In areas where other advance screening methods of CRC are not feasible, the use of FIT can be considered.